KONTRIBUSI USAHATANI PADI SAWAH TERHADAP PENDAPATAN KELUARGA DI KELURAHAN TARATARA SATU KECAMATAN TOMOHON BARAT KOTA TOMOHON - Olivia ., Bulanta; Elsje Pauline Manginsela; Welson Marthen Wangke (Sam Ratulangi University, 2019)
The purpose of this research is to find out how large the rice farming is contributed to family income. The research was conducted in December 2018 to January 2019, ranging from preparation to research Report preparation. The data used in this study are primary data and secondary data. Primary Data is derived from a direct interview with the respondent's farmer. Secondary Data is obtained from the village office of Taratara One, and internet through Google Books and Googlescholars to obtain articles of journal and thesis related to the topic of the research that is contribution of rice field farming to Family income. The sampling method was done intentionally with a total of 25 respondents. The analysis used in this study was a descriptive analysis and used the formula contributions as well as presented in the form of tables. The results showed that rice farming was an average contribution of 22.29% on family income.*eprm*